Developing an Intellectual Capital Model in the Computer Industry Based on Strategies and Outcomes Using the Grounded Theory Method - Ahmadi, Reza Baba; Chirani, Ebrahim; Mirbargkar, Seyed Mozaffar (Management Strategies and Engineering Sciences, 2024)
This research aimed to develop an intellectual capital model in the computer industry based on strategies and outcomes using the grounded theory method. The data collection tool was a semi-structured interview conducted with experts. To this end, using a purposive sampling approach (snowball sampling), interviews were conducted with 15 academic experts or senior managers of companies active in the computer industry listed on the Tehran Stock Exchange. The research data were analyzed using the coding method and Strauss and Corbin’s approach, extracting the main categories and concepts. The results indicate that, based on the study’s paradigmatic model, the causal factors of intellectual capital include capital structure, investment, production costs, quality of goods and services, competitive ability, innovation and creativity, professional ethics, commercialization of ideas, and the exchange of knowledge and experience. Contextual factors of intellectual capital include advanced technology, buyer behavior, and the competitive environment. Intervening factors of intellectual capital include market efficiency, general government policies, and the country’s developmental status. Intellectual capital strategies encompass company management policies, risk management, and supply chain management. Moreover, the outcomes of intellectual capital include production capability, sales capability, export capability, and profitability.